Control interno en el área administrativa y su incidencia en la toma de decisiones del Sindicato Cantonal de Choferes Profesionales de Valencia, Provincia - Los Ríos. Año 2021 - Endara Alescano, Jessenia Adriana (2022)
The present investigative work was carried out in the Valencia canton, which has as its objective an evaluation of internal control and the proposal of a manual of functions, policies and procedures in the administrative area. Quantitative and qualitative research was used, the research was investigated to elaborate the important data collection to meet the objectives of the research, it was necessary to apply techniques such as interview and survey without leaving behind the instrument as a questionnaire. It can be considered that the institution in the professional field is directed in a way that it can expand but internally it has conflicts, in the administrative area that is caused by the lack of internal control; The evaluation shows as a result that the institution does not have a mission, vision, which prevents reaching the objectives in the desired way, on the other hand, the lack of an organizational structure and the manual of functions, policies and procedures, carry out the elaboration and application of the questionnaires are a fundamental piece in the protection of the Union's resources, resulting in a level of confidence with 74% qualified as "moderate" while the level of control risk is qualified as "low" with 26% and the inherent risk of 13%, so it can be determined that the Union must make important corrections and provide a precise solution to each finding. Regarding the internal control and the incidence of decision-making, they were applied with the operational management indicator with 49.99% reflecting efficacy and efficiency of effectiveness for the union. A structural organization chart, a manual of functions, policies and procedures for the administrative area were established as it would help to facilitate the activities of the employees.